A Series of Imidazole Derivatives: Synthesis, Two-Photon Absorption, and Application for Bioimaging. (12th October 2015) - Zhu, Yingzhong; Xiao, Lufei; Zhao, Meng; Zhou, Jiazheng; Zhang, Qiong; Wang, Hui; Li, Shengli; Zhou, Hongping; Wu, Jieying; Tian, Yupeng
Abstract : A new series of D- π -A type imidazole derivatives have been synthesized and characterized. Two corresponding imidazolium salts (iodine and hexafluorophosphate) were prepared from the imidazole compound. Their electron-withdrawing ability can be largely tunable by salt formation reaction or ion exchange. UV-vis absorption and single-photon fluorescence spectra have been systematically investigated in different solvents. The two-photon cross sections δ 2 PA of the imidazole derivatives are measured by two-photon excited fluorescence (2PEF) method. Compared with those of T-1 (107 GM) and T-3 (96 GM), T-2 (imidazolium iodine salt) has a large two-photon absorption (2PA) cross section value of 276 GM. Furthermore, the cytotoxicity and applications in bioimaging for the imidazole derivatives were carried out. The results showed that T-1 can be used as a lysosomal tracker with high stability and water solubility within pHs of 4–6, while T-2 and T-3 can be used as probes for cell cytoplasm.